2018
DOI: 10.1155/2018/8658507
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Clusterin Is Upregulated in Nephropathia Epidemica

Abstract: Kidney insufficiency is a hallmark of nephropathia epidemica (NE). Little is known about the mechanisms of the NE kidney pathology, with current knowledge mainly based on findings in postmortem tissue. We have analyzed kidney damage biomarkers in urine collected from early- and late-phase NE using Bio-Plex kidney toxicity panels 1 and 2. To determine the disease specificity, kidney damage biomarkers were also analyzed in urine samples from patients diagnosed with gout, type 2 diabetes, systemic lupus erythemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We observed that the body weights of the mice in all groups increased (except for the 40 mg/kg treatment group on the first day after injection, Figure e), indicating that all of the groups of mice were healthy after intraperitoneal administration of SPDNs at 0, 10, and 20 mg/kg. In addition, serum alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total blood bilirubin (TBIL) activity are usually used to biochemically assess hepatotoxicity, , and blood urea nitrogen (BUN) and serum creatinine (CRAE) are correlated with nephrotoxicity. , As shown in Figure f,g, no significant differences in the ALT, ALP, TBIL, BUN, and CRAE levels were found between the control groups and C 16 -3RP nanoparticle-treated groups, indicating that C 16 -3RP nanoparticle treatment did not induce hepatotoxicity or nephrotoxicity. As shown in Figure h, compared to the control group, the liver and renal tissues after treatment with 10 and 20 mg/kg C 16 -3RP nanoparticles did not show pathological changes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We observed that the body weights of the mice in all groups increased (except for the 40 mg/kg treatment group on the first day after injection, Figure e), indicating that all of the groups of mice were healthy after intraperitoneal administration of SPDNs at 0, 10, and 20 mg/kg. In addition, serum alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total blood bilirubin (TBIL) activity are usually used to biochemically assess hepatotoxicity, , and blood urea nitrogen (BUN) and serum creatinine (CRAE) are correlated with nephrotoxicity. , As shown in Figure f,g, no significant differences in the ALT, ALP, TBIL, BUN, and CRAE levels were found between the control groups and C 16 -3RP nanoparticle-treated groups, indicating that C 16 -3RP nanoparticle treatment did not induce hepatotoxicity or nephrotoxicity. As shown in Figure h, compared to the control group, the liver and renal tissues after treatment with 10 and 20 mg/kg C 16 -3RP nanoparticles did not show pathological changes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In Northern Germany, Dobrava-Belgrade virus (DOBV) infected patients showed a diverse range of mild to moderate clinical manifestations associated with kidney injury [32]. In another study, patients with nephropathia epidemica (NE) often referred as a mild form HFRS caused by Puumala virus exhibited upregulation of biomarkers of inflammation suggested damage in kidney proximal tubule and leukocyte chemotaxis at the onset of NE in a cohort of patients in a Russian hospital [33]. On the other hand, CKDu in Sri Lanka is known to develop from tubular damage [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Clusterins are secretory glycoproteins that are involved in multiple physiopathological processes, including lipid metabolism, tissue remodelling, reproduction, transport and cell apoptosis [64]. These proteins have been classically considered as markers of cell death [65]; however, protective roles such as anti-apoptotic or prevention of complement attacking complex functions of clusterins have been suggested [66,67]. The bioinformatics analysis of the in silico inferred proteins network allowed the generation of more information from the experimental results, including data on intracellular pathways.…”
Section: Discussionmentioning
confidence: 99%